Cervical ripening and induction of labor with misoprostol vaginally - Valera, Daniel (2015)
OBJECTIVE: To determine the efficacy, colateral effects and complications of a single dose of intravaginal mysoprostol, for cervical ripening and labor induction. MATERIAL AND METHODS: The present study was carried at Hospital Loayza, between November and December, 1995. We included 30 women with intravaginall 50 m g of mysoprostol plus oxitocin as needed and 26 with oxitocin alone. RESULTS: 26 women (86,7%) with mysoprostol plus oxitocin and 9 (34,6%) with oxitocin alone had vaginal delivery (p < 0,001). The adverse effects and complications were not statistically different. CONCLUSIONS: A 50 m g single dose of vaginal mysoprostol is effective and safe for cervical ripening and labor induction.